Structure of biodegradable films at aqueous surfaces: X-ray diffraction and spectroscopy studies of polylactides and tyrosine-derived polycarbonates - Wang, Wenjie (2013)
Three representative polymers of increasing modulus, poly(D,L-lactic acid), PDLLA, poly(desaminotyrosyl-tyrosine ethyl ester carbonate), PDTEC, and the same polymer with iodinated DTE segments, PI(2)DTEC, were characterized by surface-pressure versus area (Π-A) isotherms and surface sensitive X-ray diffraction techniques. 10–100 Å thick films were prepared for these studies by spreading dilute polymer solutions at air-water interfaces. The general properties of the isotherms and the Flory exponents, determined from the isotherms, vary in accordance with the increasing modulus of PDLLA, PDTEC, PI(2)DTEC, respectively. The analysis of in-situ X-ray reflectivity and grazing incidence X-ray diffraction (GIXD) measurements from films at aqueous surfaces provides a morphological picture that is consistent with the modulus of the polymers, and to a large extent, with their packing in their dry-bulk state. Large absorption of X-rays by iodine enabled X-ray spectroscopic studies under near-total-reflection conditions to determine the iodine distribution in the PI(2)DTEC film and complement the structural model derived from reflectivity and GIXD. These structural studies lay the foundation for future studies of polymer-protein interactions at aqueous interfaces.